Conversation Initiation of Mothers, Fathers, and Toddlers in their Natural Home Environment. (May 2022) - VanDam, Mark; Thompson, Lauren; Wilson-Fowler, Elizabeth; Campanella, Sarah; Wolfenstein, Kiley; De Palma, Paul
Abstract: In a conversational exchange, interlocutors use social cues including conversational turn-taking to communicate. There has been attention in the literature concerning how mothers, fathers, boys, and girls converse with each other, and in particular who initiates a conversation. Better understanding of conversational dynamics may deepen our understanding of social roles, speech and language development, and individual language variability. Here we use large-scale automatic analysis of 186 naturalistic daylong acoustic recordings to examine the conversational dynamics of 26 families with children about 30 months of age to better understand communication roles. Families included 15 with boys and 11 with girls. There was no difference in conversation initiation rate by child sex, but children initiated more conversations than mothers, and mothers initiated more than fathers. Results support developmental theories of the different and variable roles that interlocutors play in a social context.